Effects of Low Carbohydrate High Fat Nigerian-Like Diet on Biochemical Indices in Rabbits - Oboh, Henrietta Ayodele; Olumese, Fidelis Ehidiamen (Pakistan Journal of Nutrition, 2010)
The effects of a low carbohydrate high fat Nigerian like diet on lipoprotein levels, serum electrolytes, liver and renal functions were investigated. The diet consist of 28% carbohydrate and 35% fat as percentage of total energy in a wholly compounded form. Twelve rabbits were randomly divided into two groups. The groups were: Group I that was fed the control diet and the second group II were fed with the low carbohydrate high fat diet. At the end of eight weeks, biochemical analyses were done on blood samples of the animals. There were significant (p